Students Ability to Solve Mathematical Problem Through Online Learning During Covid-19 Pandemic - Azhari, Budi; Nurhalimah, Nurhalimah; Anwar, Anwar; Abidin, Zainal (Al-Khawarizmi, 2022)
The purpose of this study is to examine the solving skill of students on mathematical problem through online learning during COVID-19 pandemic, particularly in solving the problem related area and perimeter of trapezium. Data collection is conducted by performing problem solving skill test and interview. Furthermore, the data analyses is conducted by data reduction, data presentation and conclusion formulation. This study concludes that students have very good ability to solve the problem during the online learning through whatsapp group and g-meet. Detail of the steps used in examining the problem solving abilty as follow: 1) problem comprehension; students as research subject able to explain the problem by using their own terms, analyse the problem by stating the known and unsolved variables and illustrating the provided pictures 2) planning the problem solving; subject can determine other condition from the problem, selecting and structuring the steps to solve the problems 3) implementing the problem solving; subject solved the problem by using the selected formula accordingly 4) cross-checking; subject cross-checked the solutions by using other method and compared the results.